From Knowledge To Action: Understanding The Role Of Financial Literacy In Investment Decisions Of Working Women (Journal of Informatics Education and Research, 2025)
Rationale: The rationale for this research lies in the critical relevance of financial literacy in navigating today's complex economic landscape. It is imperative to tackle the pervasive deficiency of financial literacy, especially among females, in order to promote personal welfare, social progress, and financial stability. Through a variety of strategies, such as education and policy interventions, the research tends to increase financial literacy and empower people while promoting a more just and prosperous society. Review of Literature: A variety of research on financial literacy with a focus on different locations and demographics are highlighted in it. It highlights how essential it is to implement interventions that are specifically designed to close knowledge gaps, especially for working women. There is still a lack of knowledge about how financial literacy and investing choices particularly impact working women, despite a wealth of study on these topics. In order to advance gender equality and economic empowerment through focused policies and initiatives, it is imperative to close this research gap.Research Objectives and Methodology: The focus of the research is to evaluate working women's financial literacy and determine how it affects their investing decision making. It entails a thorough analysis of the literature, the creation of theoretical frameworks, and the synthesis of current knowledge. The approach places a strong emphasis on openness, objectivity, and the iterative improvement of the theoretical framework using accessible empirical data as well as theoretical justification.Discussion and Interpretation: The study evaluated the financial literacy of working women and found that different groups of women had different levels of competency in important areas such as budgeting, debt management, investing, saving, and financial planning. Better financial management, diversified investments, and long-term planning are all associated with higher reading levels, whereas lower literacy is linked to less familiarity with investing and a dependence on untrustworthy sources. The results underscore the relevance of customized initiatives of financial literacy in enabling women to make knowledgeable choices and attain financial autonomy. Summarizing the way financial literacy influences investment choices highlights the necessity of implementing focused tactics to bridge the gender gap in investment involvement and assist women in achieving their financial objectives.Implications: As per the research, working women have varying degrees of financial literacy, which calls for specialized interventions aimed at empowering them. Programs with a specific focus should cover important topics including investing, debt management, savings, and budgeting. Women's financial independence can be increased by putting an emphasis on long-term financial objectives and granting them access to trustworthy information and guidance. Stakeholder cooperation is essential to the implementation of successful projects and their adaptation to changing needs. Working women can attain better financial outcomes and economic stability by placing a higher priority on financial literacy, confidence, and empowerment.